The representation formula for solutions of some class Hamilton–Jacobi equations - Gudynas , Gintautas (Lietuvos matematikos rinkinys, 2011)
The lower semicontinious solutions of Hamilton–Jacobi equation are contructed by Hopf formula, when hamiltonian is maximum of linear functions.
Keywords: Hamilton-Jacobi equations; lower semicontinious solutions; Hopf formula